Primitive and Traditional Art in Modern Art Theory and Practice - Novikova M. M. (Science and education: future development, 2020)
The article is devoted to identifying the points of contact between primitive and modern cultures. The subject matter is based on the theory and practice of artistic creativity, its origins and aesthetic potential. The article reveals the degree of influence of the figurative-semantic and symbolic content of primitive and traditional culture on modern artistic creativity: on stylistic, formal techniques, themes, images; in General, on artistic thinking.
Keywords: символ; графика; стиль; художественный образ; эстетика; синкретизм; скульптура; живопись; painting; sculpture; style; symbol; artistic image; graphics; традиционное искусство; aesthetics; первобытное искусство; primitive art; traditional art; syncretism